Overexpression of a New Osmotin-Like Protein Gene (SindOLP) Confers Tolerance against Biotic and Abiotic Stresses in Sesame - Chowdhury, Supriyo; Basu, Arpita; Kundu, Surekha (Frontiers in Plant Science, 2017)
Osmotin-like proteins (OLPs), of PR-5 family, mediate defense against abiotic and biotic stresses in plants. Overexpression in sesame of an OLP gene (SindOLP), enhanced tolerance against drought, salinity, oxidative stress and the charcoal rot pathogen. SindOLP was expressed in all parts and localized to the cytosol. The transgenic plants recovered after prolonged drought and salinity stress, showing less electrolyte leakage, more water content, longer roots and smaller stomatal aperture compared to control plants. There was an increase in osmolytes, ROS-scavenging enzymes, chlorophyll content, proline, secondary metabolites and reduced lipid peroxidation in the transgenic sesame under multiple stresses. The OLP gene imparted increased tolerance through the increased expression of three genes coding for ROS scavenging enzymes and five defense-related marker genes functioning in the JA/ET and SA pathways, namely Si-Apetala2, Si-Ethylene-responsive factor, Si-Defensin, Si-Chitinase and Si-Thaumatin-like protein were monitored. The transgenic lines showed greater survival under different stresses compared to control through the integrated activation of multiple components of the defense signaling cascade. This is the first report of transgenic sesame and first of any study done on defense-related genes in sesame. This is also the first attempt at understanding the molecular mechanism underlying multi-stress tolerance imparted by an OLP.